Evaluation model of coal mine emergency rescue collaborative ability based on G1-DEMATEL-measurement quantification - LIANG Yan; CHEN Hao; ZHANG Yongling; GUO Ying (Meikuang Anquan, 2022)
In order to improve the coal mine emergency rescue coordination ability of multivariate main body participation, we built an evaluation index system consisting of 5 first-level indexes and 17 second-level indexes including rescue preparation coordination, command decision-making coordination, life rescue coordination, accident handling coordination and rescue support coordination, and proposed an evaluation model of emergency rescue coordination capacity based on G1-dematel-measure quantification. The model is verified by the accident of Qinghai Chaidar Coal Mine. The results show that the coordination ability of emergency rescue is at the “general” level, in which the coordination ability of rescue preparation and rescue support is at the “good” level, and the coordination ability of command and decision, life rescue and accident disposal is at the “general” level, which is consistent with the actual situation of the rescue in Chaidar Coal Mine. It shows that the evaluation model can not only objectively evaluate the emergency rescue coordination capacity, but also analyze the weak links of the emergency rescue coordination capacity, providing decision support for the emergency rescue coordination capacity construction.